Families and technologies. What about the phubbing in Mexico? - Evelyn Téllez Carvajal (Jesuit University Ignatianum in Krakow, 2017)
RESEARCH OBJECTIVE: The aim of this article is to call the attention to specific social behaviors that have been generated by the indiscriminate use of the technologies. We want to make evident that those behaviors cause a detriment of the communication between the members of the Mexican families, causing in consequence that minors are being neglected by parents and the lack of adequate parental control in the face of the risks associated with the use of certain technologies. THE RESEARCH PROBLEM AND METHODS: The presented study involves the relation between people's behaviors related to their access to certain technologies face to the concept of family and its importance in the society for an interconnected world. We make an in-depth study of the academic and informative literature which deals with the phenomena called phubbing. We refer to varied research, both technical and empirical and applied the inductive method and critical analysis, taking into consideration previous official, as well as non-official, researches that demonstrate phubbing adverse effects in communication between Mexican family's members. THE PROCESS OF ARGUMENTATION: In the first part of the research we defined the concept of family in Mexican Law and how the political agenda proposes the use of technologies in order to have a greater development of the society that can turn in better opportunities and conditions of life of the individuals in general and families in particular. In a second part we refer the specific Internet penetration in Mexico as a consequence of the above mentioned agenda. Finally, in a third part, we analyze the phenomena called phubbing and its impact in Mexican Families that is the essential part of our argumentation. RESEARCH RESULTS: The result of this argumentation ends to some advices that deal with better practices in the usage of technologies in order to prevent adverse effects in Mexican families without renouncing to the incorporation of technologies in our daily life routines. CONCLUSIONS, INNOVATIONS AND RECOMMENDATIONS: Even though the consequences of phubbing in our society are evident, we cannot yet accurately count its effects. There are data regarding the time that parents spend with their children compared to the average time they spend using applications, video games, e-mail, social networks, and media in general. The disorganization in the time we spend in leisure, work and family life turns evident. This situation invites us to reflect about the role technologies play in relation to our family integration or disintegration. Hyper-connectivity has generated adverse conditions for individuals, both physical and psychological, that result in an affection towards the fundamental pillar of our society that is the family. It is noted that the Mexican government needs to face the growing wave of phubbing, by informing its society about the risks of the abuse of the use of technologies in one hand, and to promote programs to invite people to a more conscious access to social networks by best practices of the other. Only in that way we can grant the principle of freedom and family autonomy in Mexico. Otherwise, how can we refer to a family autonomy if its members that make up the core of society have stopped communicating?